Blended Learning: Pembelajaran Abad 21 sebagai â€˜Jalan-Tengahâ€™ Menjaga Kualitas Pendidikan Di Era Pandemi Covid-19 - Dian Nuri Ningtyas; Adison Adrianus Sihombing (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2023)
COVID-19 has transformed the holistic learning process into an online platform. Unfortunately, these changes are only â€œEMERGENCYâ€ responses because they occur under conditions of unpreparedness. This unpreparedness is experienced at all levels, both educational institutions, teachers, students and parents. As a result, online learning is considered less effective and there is strong pressure from various parties for schools to reopen offline education methods even though the pandemic has not passed. This study aims to show the existential problems experienced by students, teachers, and parents in transforming the educational paradigm. This research is qualitative, using primary and secondary data. Primary data was obtained through Google forms and in-depth interviews via WhatsApp. Respondents consisted of students, parents and teachers in the primary education stage in the DKI Jakarta area. Each group of respondents consists of fifteen people. The data is analyzed through the restatement, description and interpretation stages. This research shows that online learning has not been an effective solution to learning during the pandemic, because the response given is simply about technological change, not seen as a change in tradition towards 21st-century learning. In the current pandemic conditions and the urge to reopen the school, blended learning is a wise choice as a resolution, so that the quality learning process can be maintained. Increasing the digital literacy skills of teachers and conducting socialization to increase public awareness of the importance of transforming educational culture from offline-based learning to IT-based learning both Online and blended learning methods.